Non-Genetically Improving the Natural Cytotoxicity of Natural Killer (NK) Cells - Villalba, Martin; Alexia, Catherine; Bellin-Robert, Anais; Fayd'herbe de Maudave, Alexis; Gitenay, Delphine (Frontiers in Immunology, 2020)
The innate lymphocyte lineage natural killer (NK) is now the target of multiple clinical applications, although none has received an agreement from any regulatory agency yet. Transplant of naïve NK cells has not proven efficient enough in the vast majority of clinical trials. Hence, new protocols wish to improve their medical use by producing them from stem cells and/or modifying them by genetic engineering. These techniques have given interesting results but these improvements often hide that natural killers are mainly that: natural. We discuss here different ways to take advantage of NK physiology to improve their clinical activity without the need of additional modifications except for in vitro activation and expansion and allograft in patients. Some of these tactics include combination with monoclonal antibodies (mAb), drugs that change metabolism and engraftment of specific NK subsets with particular activity. Finally, we propose to use specific NK cell subsets found in certain patients that show increase activity against a specific disease, including the use of NK cell line derived from patients.